Otimização do processo de montagem de componentes eletrônicos de superfície utilizando ferramenta multicritério - CASTRO, Anderson de Oliveira (Universidade Federal do Pará, 2017)
The optimization problems of industrial process attracted many researches since the early 90's of the last century. The production volume increase, market competition increase and technological advances pushed the industries to seek for low cost and quick implementation solutions. One of the processes that became the core reason for increasing the sales volumes was the surface mount technology composed by printing, automated chip mounting and reflow oven which replaced the through hole technology. This research formulated a new point of view for optimization of modular chip mounters based on the already known feeder assignment problem and assembly head motion problem applying the global optimization using the non sorting dominance genetic algorithm the NSGAII in regard of the total cycle time reduction. The modeling of the fitness functions was presented and the multi criteria optimization tool was described using the machine functions and constraints. The same method could be applied to describe other type of machines to support future research.